Optimization strategy of distribution network operation considering multi-investment entities under the situation of ubiquitous power Internet of things - Xiaodong SHEN; Junyong LIU; Shuai HU; Ping RAO; Mai HE (物联网学报)
The ubiquitous power Internet of things encourages a large number of new power equipment, such as distributed power supply, energy storage and electric vehicles, to connect to the distribution network.With the increasing penetration of renewable energy in the distribution network and the gradual opening of the electricity market, the investment entities of the power grid tend to be diversified.The uncertainty of the access of renewable energy to the power grid and the coordination of the interests of various entities resources is increasingly prominent.Considering the profits of distributed energy resources (DER) investors in the regional distribution network, an optimal operation strategy based on the incentive mechanism in ubiquitous power Internet of things was proposed.This strategy could reduce the adverse effects of load fluctuations and reversed power flow on the power grid, while increasing profits for DER investors.The calculation example shows the effectiveness of the proposed method.